Suspension of concentrated fine particles with novel axial and radial impellers / Wong Siau Dhing - Wong, Siau Dhing (2013)
This project was on the suspension of fine particles in a fully-baffled flat-based cylindrical stirred tank of 155mm diameter using novel impeller designs by SATAKE Chemical Equipment MFG. LTD. as compared to a standard 4 pitched-blade impeller (4PBT) and 3-blade propellers (3P). The SATAKE impellers are an axial 3-blade HR100, a unique radial 4-blade HS604 and a large 2-blade MR203 impeller. The particles were (poly)methyl-methacrylate (PMMA) of diameters 18.6, 75.2 and 140.6 μm (SW, MW and LW, respectively) at concentrations 5, 10, 15, 20, 30 and 40% by weight, suspended in water filled to a height that gives 1:1 aspect ratio. Impeller clearance from the base were set at C/D=0.25, 0.50, 0.75 and 1.0, except for the HS604 and MR203 which were used only at an especially low clearance of C/T=0.02. Increasing the clearance led to increased Njs and ɛjs for all cases with very few exceptions between C/D=0.25 and 0.5 with the 4PBT. The HR100 and 3P of smaller diameter (d60) were the least affected by the clearance. The effect of clearance was also least significant with the MW particles; and suspending the SW particles required higher speed and energy with all impellers. Increasing particle concentration also led to higher speed and energy to achieve suspension, but again the HR100, HS604 and 3P (d60) were the least affected by the concentration change. These impellers were also the most efficient in terms of power requirement for just-suspension. The MR203 was the least efficient among all impellers, but its geometry is also very different and not designed for solid suspension. The flow pattern generated from the impeller geometry directly affects the distribution of solids on the base, which in turn determine the speed and energy required to achieve suspension. S values obtained from Zwietering’s equation show the strong effect of clearance, particle size and concentration in the cases studied, which implies that the accuracy of prediction with Zwietering equation can be much affected by differences in any of the operating parameters.